Obsolete but dangerous antacid preparations. Issue 627 (January 1978) - Robson, R. H.; Heading, R. C.
Abstract : One case of acute hypercalcaemia and two of recurrent nephrolithiasis are reported in patients who had regularly consumed large amounts of calcium carbon-ate-sodium bicarbonate powders for more than 20 years. The powders had been obtained from pharmacists unknown to the patients' medical practitioners. It is suggested that these preparations were responsible for the patient's problems, and that such powders should no longer be freely obtainable.